Statistical Model for Assessing the Impact of Targeted, School-based Dental Sealant Programs on Sealant Prevalence Among Third Graders in Ohio - Sunny Kim, PhD; Amy M. Lehman, MAS; Mark D. Siegal, DDS, MPH; Stanley Lemeshow, PhD (Blackwell Synergy, 2003)
Since Ohio school-based dental sealant programs target economically disadvantaged groups, simple comparison of sealant prevalence between schools with sealant programs and those without is problematic due to underlying disparities between the two in sealant prevalence. The goal of our analysis was to estimate the impact of sealant programs on sealant prevalence among third graders in Ohio by applying a statistical model to data from a 1998-99 Ohio oral health screening survey of schoolchildren to control for differences in background characteristics